Drosophila SOCS Proteins. (13th December 2011) - Stec, Wojciech J.; Zeidler, Martin P.
Abstract : The importance of signal transduction cascades such as the EGFR and JAK/STAT pathways for development and homeostasis is highlighted by the high levels of molecular conservation maintained between organisms as evolutionary diverged as fruit flies and humans. This conservation is also mirrored in many of the regulatory mechanisms that control the extent and duration of signalling in vivo . One group of proteins that represent important physiological regulators of both EGFR and JAK/STAT signalling is the members of the SOCS family. Only 3 SOCS-like proteins are encoded by the Drosophila genome, and despite this low complexity, Drosophila SOCS proteins share many similarities to their human homologues. SOCS36E is both a target gene and negative regulator of JAK/STAT signalling while SOCS44A and SOCS36E represent positive and negative regulators of EGFR signalling. Here we review our current understanding of Drosophila SOCS proteins, their roles in vivo, and future approaches to elucidating their functions.